CULTURAL CSR IN PERCEPTIONS OF CULTURAL PRESERVATION OSING - daniar paramita, ratna wijayanti; Taufiq, Muchamad; Rizal, Noviansyah (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2018)
aim of this study is to obtain a model of the development of Corporate Social Responsibility Â culture that will be used by companies as a form of participation of indigenous cultural preservation Osing tribe. This study analyzes the public response to the social awareness of the cultural aspects of the company, to explore and understand the cultural values that exist in society Kemiren village for the preservation of indigenous culture. So the paradigm in this study is ethnometodology interpretive approach. The results of this research to the development of culture through the implementation of the ceremonies, each group of informants have the same perception, that the ceremony is a ritual and custom that must be implemented. The shape of the execution in accordance with the ritual that had been implemented, with funding coming from the individual and society through muphu (dues). To the development of culture through the development of art galleries, each group of informants have different perceptions; Culturalactors:they feel the studio that they have never received funds, whether from the government or from the company. Funding for the development of art galleries, either for exercise or to perform (b-fest or staging) is carried out by independent fee. Culturalfigures:they are self-financed owner of the art galleries, should they get help for example in the form of equipment. TheGovernment:government provides assistance in the form of actualization of art. The galleri was given the freedom to create and actualize in art. Model CSR developed in this study to seek the establishment of effective communication between the company, CSR forum, council Blambangan arts and cultural actors/ art galleries owner. With the development of the model is expected later CSR funds disbursed by the company through Art board blambangan (DKB) or directly to the cultural actors/ art galleries owner as sponsorship or development of art galleries can be precisely targeted.Â Keywords: Corporate Social Responsibility culture, custom culture Osing, culture actors, art gallery